2001
DOI: 10.1046/j.1432-1327.2001.02064.x
|View full text |Cite
|
Sign up to set email alerts
|

An element within the 5′ untranslated region of human Hsp70 mRNA which acts as a general enhancer of mRNA translation

Abstract: The untranslated regions of mRNAs encoding heat-shock proteins have been reported to contain elements important to the post-transcriptional regulation of these key components of the stress response. In this report we describe an element from the 5 H UTR of human Hsp70 mRNA that increases the efficiency of mRNA translation. Cloning of this region upstream of the coding sequence of two different reporter genes (firefly luciferase and chloramphenicol acetyltransferase) increases expression of the reporter under n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 37 publications
3
37
0
1
Order By: Relevance
“…No large section of the 5Ј-UTR can be excised without a dramatic deleterious effect on the expression of the second cistron. This conclusion nicely correlates with data of Vivinus et al (9), who have recently shown the importance of the integrity of Hsp70 5Ј-UTR for its enhancing effect on translation of reporter genes in monocistronic constructions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…No large section of the 5Ј-UTR can be excised without a dramatic deleterious effect on the expression of the second cistron. This conclusion nicely correlates with data of Vivinus et al (9), who have recently shown the importance of the integrity of Hsp70 5Ј-UTR for its enhancing effect on translation of reporter genes in monocistronic constructions.…”
Section: Discussionsupporting
confidence: 91%
“…The attempts to experimentally identify a specific structure within the relatively short 5Ј-UTR of BiP mRNA (210 nt) have been unsuccessful (7). Even more surprising is that the 5Ј-UTR of mammalian Hsp70 mRNA has been reported to be devoid of IRES properties (8,9), despite the fact that its length, GC-content, and relaxed cap-dependence (10,11) are similar to the 5Ј-UTR of BiP mRNA, and the corresponding mRNAs encode proteins with related functions (chaperones). The high GϩC content of the 5Ј-UTR of mammalian Hsp70 mRNA seems more compatible with operation via an IRES than by means of the classical scanning mechanism.…”
mentioning
confidence: 99%
“…We propose that the 5Ј UTR of the emp2 transcript harbors an element(s) important for its efficient translation. It has been demonstrated in both Drosophila and human that a lengthy and intact 5Ј UTR is required for the preferential translation of hsp70 transcripts under stress conditions (Lindquist and Petersen, 1990;Hess and Duncan, 1996;Vivinus et al, 2001). If the 5Ј UTR of emp2 has a function similar to that of hsp70, this may provide a mechanism to regulate the accumulation of EMP2 in response to heat stress, assuming that emp2 is transcribed constitutively (data not shown).…”
Section: Mu Transposon Insertion Correlates With the Use Of Alternatimentioning
confidence: 94%
“…There are examples of a posttranscriptional regulatory role for the 5ЈUTR. The 5ЈUTR of human heat shock protein 70 mRNA contains an element that increases the translation efficiency at 42°C compared with at 37°C (37). Relatively little is known about the role(s) of selective expression of mRNAs differing only in the 5ЈUTR.…”
Section: Cd3mentioning
confidence: 99%